Model Validation of Biomass-Coal Blends Co-Pyrolysis to Produce Hybrid Coal - Zahra, Aghietyas Choirun Az; Prasetyo, Hendi Aviano; Rizkiana, Jenny; Wulandari, Winny; Sasongko, Dwiwahju (Purnomo Yusgiantoro Center, 2019)
Co-pyrolysis of coal and biomass blend to produce hybrid coal has recently been experimentally studied by some previous researchers. For similar generated energy, a newly developed hybrid coal is claimed to be more environmentally friendly compared to the coal only due to the release of neutral CO2. To acquire a better understanding of co-pyrolysis of coal and biomass blend, an experiment had been carried out in a tubular furnace reactor. For this purpose, the blends of constant mass composition of 20 wt% sawdust and 80 wt% low-rank coal were used throughout the study. It was found from the experiment that approximately 42.1% carbon, and 1.6% of ash were produced from the co-pyrolysis blend. Then, a steady state simulation of co-pyrolysis was developed using Aspen Plus v8.8 to predict the hybrid coal carbon content and required heat to perform the co-pyrolysis. The model simulation showed that hybrid coal yielded 44.0% carbon, which was at 4.5% deviation from the experimental study. The model had also been successfully used to estimate heat required to produce hybrid coal. It predicted that the equivalent heat of 336.2 kW was required to produce hybrid coal from 1,000 kg/h blend feed. The heat generated by the modeling of sawdust biomass combustion for fuel purposes was also estimated to supply heat for endothermic co-pyrolysis. It was found that 1,000 kg/h sawdust was predicted to be equivalent to 371.4 kW. This suggests that for scaling up purpose, ratio of sawdust fuel to blend feed of 1:1.1 is sufficient for this process.